Blue, Black, and Stripes: Evolution and Development of Color Production and Pattern Formation in Lizards and Snakes - Kuriyama, Takeo; Murakami, Arata; Brandley, Matt; Hasegawa, Masami (Frontiers in Ecology and Evolution, 2020)
In order to understand molecular and genetic mechanism of color pattern formation, not only adult phenotypes but also processes and mechanisms of color production and pattern formation during embryonic and postembryonic stages should be described. The pigment cell based color production and pattern formation during embryogenesis were reviewed for the recent studies on lizards and snakes, by focusing on different color production mechanisms in terms of epidermal and dermal pigment cell architectures, and then discuss the genetic determinants of pattern formation considering both biologically relevant theoretical models which consider pigment cell specification, migration, and architecture differentiation. Clarifying the contributions of pigment cells and genetic factors improves our general understanding of reptilian color pattern evolution.